Analysis of Patterns of Leadership Regeneration with the Church Today - Georges Nicolas Djone; Ricardo Mansyur Simamora; Bezaleal Robert Sudarto; Perwint; Gibson Parlindungan (East Asian Journal of Multidisciplinary Research, 2022)
This paper aims to analyze the patterns of leadership regeneration found in the Church today, using a descriptive qualitative method approach by collecting data through biblical literature, books, various journals, and interviews. Leadership within the Church today uses an allegedly less effective pattern for the long-term continuity of church life because regeneration is not a priority, so the younger generation feels that it is not counted as part of the Church's development plan day and in the future. Thus they do not feel at home but judge themselves as strangers within the Church. As a result, the pattern of leadership regeneration within the Church today is one of the triggers for the gap between generations that actually gives birth to a form of indirect division within the community of believers as the Body of Christ.